Storytelling, Verbal Fluency, and Teacher’s Perception of Primary School Spanish Students - Giuseppe Iandolo; Miguel Aroca-Salom; Ángeles Esteban; Gustavo Gonzalez-Cuevas; Cristina Alonso-Campuzano (SAGE Open)
During childhood, teachers’ perception of students’ behavioral and academic performance, as well as storytelling and verbal fluency are of special relevance for reaching cognitive developmental milestones. However, little is still known about the interplay between these factors for students’ success. This investigation aimed at exploring narrative skills, verbal fluency, and teachers’ perception of behavioral and academic performance in sixty-one students aged between 6 and 12 years old from a Spanish primary school. The NEPSY-II verbal fluency test and the Bears Family Projective test were administered to students and an ad-hoc questionnaire about pupils’ socioemotional and academic progress in the classroom was completed by their teachers. Students’ stories were audio-recorded and transcribed verbatim, coded, and analyzed using the Bears Family Integrated System. The results demonstrated that these teachers perceived girls with more typical behavior than boys in class. In general, students’ narrative skills were globally related to their academic and behavioral performance as perceived by their teachers. Students that used in storytelling the family as a unit were perceived by their teachers as happier. However, wider verbal fluency in students was unrelated to cohesion and structure in the stories, and only significantly related to more episodes and characters. Finally, students perceived by their teachers with lower academic performance and less typical behavior told more unbalanced stories with more characters’ maladaptive behaviors. In conclusion, these results highlight the importance of measuring verbal fluency and storytelling skills by teachers in primary education as potential risk/protective markers for emotional and behavioral self-dysregulation in class.